Agricultural Biomass Based Potential Materials 2015
DOI: 10.1007/978-3-319-13847-3_15
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Use of Coir, Almond, Apricot, Argan, Shells, and Wood as Reinforcement in the Polymeric Matrix in Order to Valorize These Products

Abstract: The natural resource materials have an exceptional potential as reinforcement in plastic composites, due to their low cost, good mechanical properties, and biodegradability. This chapter is related to the use of some natural resources (nutshells residues) and their effect on polymer composite with varying filler reinforcement content and type or improving the adhesion between polymer matrix and filler. In this study, the used natural resources as bio-filler were almond shells, coir shells, argan shells, aprico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…). The solidified polymer layer at the walls combined with the expanded central material leads to the pronounced curvature of the flow front centerline . It was also observed that the viscosity tends to be constant along the mold width as shear rate increases.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…). The solidified polymer layer at the walls combined with the expanded central material leads to the pronounced curvature of the flow front centerline . It was also observed that the viscosity tends to be constant along the mold width as shear rate increases.…”
Section: Resultsmentioning
confidence: 95%
“…Although the mold temperature can be increased, this will increase the cooling cycle time so a compromise must be made. The distance that the material can flow (short shot) is also related to the processing conditions taking into account the rheological properties of each material . An optimized injection molding process requires an accurate control of several parameters such as the melt temperature, melt viscosity, shear rate, mold temperature, injection speed, injection pressure, and switch over point for speed and pressure to reduce the cycle time .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations